1996
DOI: 10.1029/95ja03672
|View full text |Cite
|
Sign up to set email alerts
|

Cross polar cap diameter and voltage as a function of PC index and interplanetary quantities

Abstract: Measurements of precipitating particles and the electric field on board EXOS D spacecraft for the period January–June 1990 have been used for estimation of the diameter of the polar cap along dawn‐dusk meridian and the polar cap voltage. Identification of the polar cap boundaries has been made on the basis of specific features of precipitating ions. The data on the polar cap boundary location obtained for different geophysical conditions have been used to derive the statistical relationship between the polar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 24 publications
9
116
2
Order By: Relevance
“…One also has to note that the Ridley and Kihn (2004) work is limited to PCN<4-5 for winter and <3-4 for summer and this could account for some differences with our results. In terms of the linear slope, the SuperDARN data reported here are also consistent with the satellite-based CPCPs of Troshichev et al (1996) who reported the value of 19.35 kV/PCN.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…One also has to note that the Ridley and Kihn (2004) work is limited to PCN<4-5 for winter and <3-4 for summer and this could account for some differences with our results. In terms of the linear slope, the SuperDARN data reported here are also consistent with the satellite-based CPCPs of Troshichev et al (1996) who reported the value of 19.35 kV/PCN.…”
Section: Discussionsupporting
confidence: 78%
“…To assess these dependencies, we performed linear fitting to the growing trend at small values of a respective parameter (obtained fit parameters are reported in Table 1) and asymptotic exponential fitting (red lines, obtained fit parameters are reported Ridley and Kihn (2004) through AMIE modeling. The yellow line is the linear relationship reported by Troshichev et al (1996). (e) The same as in (a) but for the Newell coupling function Ec.…”
Section: Cpcp As a Function Of E Kl Pcn And E Cmentioning
confidence: 74%
See 3 more Smart Citations